Direct Identification of Aerobic Bacteria by Matrix‐Assisted Laser Desorption Ionization Time‐of‐Flight Mass Spectrometry Is Accurate and Robust. Issue 5 (14th December 2015) - Mestas, Javier; Quias, Teephany; Dien Bard, Jennifer
Abstract : Background: Bacterial identification in the clinical laboratory can be laborious and expensive. Matrix‐assisted laser desorption ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS) is a rapid and cost‐effective diagnostic tool for the identification of organisms routinely found in the microbiology laboratory. The objective of this study was to demonstrate that identification of aerobic Gram‐positive and Gram‐negative organisms could be performed accurately and efficiently by MALDI‐TOF MS and the Bruker Biotyper system without the use of time‐consuming extraction methodologies. Methods: Isolates previously recovered by routine culture and workup from clinical specimens were cultured to appropriate media, identified directly by MALDI‐TOF MS, and compared to results from various biochemical identification methods. Results: Using the direct‐smear method, 99.5% and 98.0% of aerobic Gram‐negative and Gram‐positive bacteria, respectively, were identified to the genus level. At a score of ≥1.9, 97.6% Gram‐negative organisms and 94.6% Gram‐positive organisms were correctly identified to the species level by direct‐smear method. Only 1.1% of isolates required further reflex to direct‐plate extraction. The direct‐smear method proved to be robust, as various growth temperatures, media, culture age, and different operators had no notable impact on the bacterial identification rate. Conclusion: The direct‐smear method is an accurate and time‐saving method for routine species‐level bacterial identification.